RFID based sensor platform for industry 4.0 application - Petrov, Dmitry; Schmidt, Marco; Hilleringmann, Ulrich; Hedayat, Christian; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Determinant groups of Hermitian lattices over local fields - Kirschmer, Markus (Archiv der Mathematik)
We describe the determinants of the automorphism groups of Hermitian lattices over local fields. Using a result of G. Shimura, this yields an explicit method to compute the special genera in a given genus of Hermitian lattices over a number field.
Keywords: General Mathematics

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Proof-Carrying Hardware Versus the Stealthy Malicious LUT Hardware Trojan - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Applied Reconfigurable Computing)
Reconfigurable hardware has received considerable attention as a platform that enables dynamic hardware updates and thus is able to adapt new configurations at runtime. However, due to their dynamic nature, e.g., field-programmable gate arrays (FPGA) are subject to a constant possibility of attacks, since each new configuration might be compromised. Trojans for reconfigurable hardware that evade state-of-the-art detection techniques and even formal verification, are thus a large threat to these devices. One such stealthy hardware Trojan, that is inserted and activated in two stages by compromised electronic design automation (EDA) tools, has recently been presented and shown to evade all forms of classical pre-configuration detection techniques. This paper presents a successful pre-configuration countermeasure against this ``Malicious Look-up-table (LUT)''-hardware Trojan, by employing bitstream-level Proof-Carrying Hardware (PCH). We show that the method is able to alert innocent module creators to infected EDA tools, and to prohibit malicious ones to sell infected modules to unsuspecting customers.

Conception of a digital Sales Bonus System based on Blockchain Technology - N., N.

Textaufgaben lesen und verstehen lernen – Entwicklungsforschungsstudie zur mathematikspezifischen Leseverständnisförderung - Dröse, Jennifer

Scaffolding für fachbezogene textsortenspezifische Lesestrategien – Entwicklungsforschungsstudie zur Förderung des Umgangs mit Textaufgaben - Dröse, Jennifer; Prediger, Susanne (Fachunterricht, Sprachbildung und Sprachkompetenzen)

Know your analysis: how instrumentation aids understanding static analysis - Schubert, Philipp; Leer, Richard; Hermann, Ben; Bodden, Eric (Proceedings of the 8th ACM SIGPLAN International Workshop on State Of the Art in Program Analysis - SOAP 2019)